Masting effect on alpha and beta avian diversity in fragmented forests of relict-endangered Mexican Beech (Fagus grandifolia subsp. mexicana) - Rodríguez-Ramírez, Ernesto C. (2021)
Abstract Background: Tropical montane cloud forests are one of the most important hotspots on Earth and show presence of relict-endemic and endangered species, representing about 14% of the total tropical forest worldwide. Synchronous seed production or masting in tropical montane cloud tree species is a widespread reproductive strategy of decidu‐ ous and evergreen broad-leaved tree associations to decrease costs of reproduction and ensure ofspring. Masting event maintains a high avian diversity, which can be modifed by phenological process (seed production and non- seed production). Methods: The main aim of this study was to assess alpha and beta avian diversity and whether the composition of the trophic guild modifes among phenological processes and between two fragmented relict-endangered Mexican Beech (Fagus grandifolia subsp. mexicana) forests (Medio Monte and El Gosco) in the Mexican state of Hidalgo. In addi‐ tion, we evaluated beechnut production. Results: We recorded 36 bird species, 11 of them included in some conservation risk status, and 5 endemic species. Alpha diversity values were dissimilar in avian richness (q=0) among phenological processes and between frag‐ mented beech forests. Avian communities among three phenological processes and between fragmented forests were structurally similar, dominated during immature seeds the Brown-backed Solitaire (granivores–insectivores– frugivores); during mature seeds the White-crowned Parrot (Pionus senilis, granivores–frugivores); and the Dwarf Jay (Cyanolyca nana, insectivores) was abundant during low seed quality. The complementarity index was high among phenological processes and low between forests. We found a high bird turnover value between immature seeds— mature seeds and during mature seeds—low seed quality. Furthermore, a similar pattern was recorded between the two study forests. Seed production showed a high number of undamaged beechnuts in Medio Monte, while in El Gosco beechnuts were attacked by insects. Conclusions: Our results refect that masting phenological process and contrasting study forests’ structure infuence the shifts in alpha and beta diversity of seed and non-seed bird consumers. Our study reafrms the importance of continuing studies throughout masting in all the Mexican Beech forests to address regional eforts in preserving the relict-ecological interactions.